2014
DOI: 10.1002/ppap.201400001
|View full text |Cite
|
Sign up to set email alerts
|

Morphology Transformations of Platelets on Plasma Activated Surfaces

Abstract: Improved hemocompatibility from the perspective of platelets adhesion and activation on polyethylene terephthalate surfaces has been addressed. The activation stage of platelets has been determined from their size and morphology using scanning electron microscopy (SEM). The activation of platelets on untreated polymer materials was very intensive. Polymer materials were treated with weakly ionized oxygen plasma in order to repel platelet adhesion. Already short treatment times (3s) showed significant reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…The polymers without any antithrombogenic surface finish therefore adhere blood platelets and cause their activation as observed in Figure 3. neutral oxygen atoms is therefore beneficial and results are similar to those obtained by treatment of this polymer in oxygen plasma [24,25]. The poor ability for adhesion of blood platelets on oxygen-functionalized materials has been explained by different conformation of blood proteins that adhere to the surface of PET polymer in a fraction of a second after incubating with fresh blood, so well before any platelet adheres and activates [26].…”
Section: Resultssupporting
confidence: 55%
“…The polymers without any antithrombogenic surface finish therefore adhere blood platelets and cause their activation as observed in Figure 3. neutral oxygen atoms is therefore beneficial and results are similar to those obtained by treatment of this polymer in oxygen plasma [24,25]. The poor ability for adhesion of blood platelets on oxygen-functionalized materials has been explained by different conformation of blood proteins that adhere to the surface of PET polymer in a fraction of a second after incubating with fresh blood, so well before any platelet adheres and activates [26].…”
Section: Resultssupporting
confidence: 55%
“…Results regarding hemocompatibility have been obtained by other researchers as well. Modic et al studied platelet adhesion on surfaces treated in pure oxygen plasma and found these surfaces to have excellent hemocompatibility properties . In contrast, Kolar et al and Primc et al studied the influence of nitrogen and ammonia plasma treatment on platelet adhesion and found worse hemocompatibility in comparison with that produced by oxygen plasma treatment .…”
Section: Resultsmentioning
confidence: 99%
“…Modic et al studied platelet adhesion on surfaces treated in pure oxygen plasma and found these surfaces to have excellent hemocompatibility properties. [6] In contrast, Kolar et al and Primc et al studied the influence of nitrogen and ammonia plasma treatment on platelet adhesion and found worse hemocompatibility in comparison with that produced by oxygen plasma treatment. [5,26] However, the hemocompatibility of surfaces treated in nitrogen and ammonia plasma still appears to be better than that produced by SO 2 or H 2 S plasma treatments.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations